Secondary myoadenylate deaminase deficiency is not a common feature of inflammatory myopathies: A descriptive study - Wilkinson, Michael; Cash, Kathy; Gutschmidt, Bernice; Otto, Sophia; Limaye, Vidya (Frontiers in Medicine, 2022)
Background Myoadenylate deaminase (MAD) deficiency is a form of metabolic myopathy, which generally causes only mild symptoms in the primary inherited form. Inflammatory myopathies are a group of autoimmune diseases which result in skeletal muscle weakness. In addition to inflammatory pathology, it has been speculated that non-inflammatory mechanisms, and possibly secondary MAD-deficiency, may potentially contribute to weakness in these conditions. Methods We investigated for an association between these two myopathic processes through two complementary methods. Firstly, muscle biopsy records in South Australia over a 17-year period were retrospectively reviewed for diagnosis of myositis or MAD-deficiency, as well as associated clinical features. Secondly, a prospective arm histochemically tested all incident biopsy specimens over a 12-month period for MAD-deficiency. Results In the retrospective arm, 30 MAD-deficient cases were identified (1.3% of all biopsies), with no significant difference observed in overall rates of myositis diagnosis between patients with intact and deficient MAD activity (21.3% vs 26.7%, P = 0.47). No cases of MAD-deficiency were detected in the prospective arm, despite 39 cases of myositis being identified over this period. Conclusion Secondary MAD deficiency is unlikely to be a major driver of symptoms in inflammatory myopathies.